E.T. [videorecording (DVD)] the extra-terrestrial - Stone, Dee Wallace, 1948-; Coyote, Peter; Barrymore, Drew; Thomas, Henry, 1971- (Universal Pictures Home Entertainment, 2019)
Relive the adventure and magic in one of the most beloved motion pictures of all-time, from Academy Award-winning director Steven Spielberg. Captivating audiences of all ages, this timeless story follows the unforgettable journey of a lost alien and the ten-year-old boy he befriends.